BUPATI PEREMPUAN PERTAMA DI LAMPUNG DAN KEGAGALAN CALON PETAHANA PADA PILKADA DI LAMPUNG TIMUR TAHUN 2015 - Hertanto Hertanto; Handi Mulyaningsih (Program Studi PPKn FIS UNJ & Asosiasi Profesi PPKn Indonesia, 2017)
In Indonesia, women were elected as governors, regents, mayors and deputy regional head is still small. The same phenomenon occurred in Lampung during the election period of 2005-2014, not a single female candidate was elected as regional head and deputy regional head. New on the elections in 2015 elected two women as East Lampung Regent (Chusnunia Chalim) and Vice Regent of Pesisir Barat (Erlina). The purpose of this study to determine the factors Chusnunia Chalim victory (and a couple Zaiful Bokhari) in local elections in East Lampung district in 2015. Theoretical framework used to explain the modalities of political contestation of the election, assuming that the candidate that wins must have the capital that includes political capital, social capital, and economic capital. This study used a descriptive approach qualitative research informants the winning team mate Chusnunia Chalim and Zaiful Bokhari, Commissioner of the East Lampung Regency, local community leaders, and some leaders of political parties bearers and supporters of the candidate. Discussion of the results showed that women's involvement in political elections and local governments began to seem real. Chusnunia because social capital is consolidated with the political capital of the bearers of political parties (PKB and PD) and the PDI-P supporters of political parties. This victory more dominant factor in social capital and strengthened by the political capital that appears at times the last round of the campaign. Social capital is obtained from the ethnic affiliation of voters with candidates and religious culture of the majority of the population of East Lampung. Meanwhile, the advantage of the element of political capital gained from the failure of incumbent candidates in the voting stage. So that prospective incumbent and its main bearers of political parties, PDI-P, shift support to Chusnunia.